PHENOTYPING CHOROIDEREMIA AND ITS CARRIER STATE WITH MULTIMODAL IMAGING TECHNIQUES. (2017) - Ma, Kevin K.; Lin, James; Boudreault, Katherine; Chen, Royce W. S.; Tsang, Stephen H.
Abstract : Purpose: To describe findings in a patient with choroideremia (CHM) and his mother, an obligate CHM carrier. Methods: Case report. Results: A 25-year-old man with nyctalopia and poor peripheral vision since childhood, as well as a family history consistent with an X-linked retinal disorder was diagnosed with CHM. His asymptomatic 50-year-old mother, an obligate carrier, was also examined. Fundus examination of the affected man showed significant atrophy of the choroid and retinal pigment epithelium, whereas the carrier woman showed patchy pigmentary mottling. Imaging of the affected man showed diffuse retinal pigment epithelium atrophy on optical coherence tomography and extensive areas of decreased choriocapillaris flow on optical coherence tomography angiography. By contrast, the carrier woman showed subtle retinal pigment epithelium changes on optical coherence tomography and mild flow alterations on optical coherence tomography angiography. Conclusion: This case demonstrates the findings seen in CHM, and while CHM carrier women are often asymptomatic, they may exhibit a mosaic pattern of pigmentary change on fundus examination. Optical coherence tomography angiography may show mild choroidal flow abnormalities. This finding serves to further characterize the extent of dysfunction in CHM and its carrier state. Abstract : The authors present a case report of a 25-year-old man with choroideremia and his 50-year-old mother who is an obligate choroideremia carrier. The phenotypic findings using multimodal imaging techniques are described.